Feeding practices and nutritional status of HIV-exposed and HIV-unexposed infants in the Western Cape - Magdel E. Rossouw; Morna Cornell; Mark F. Cotton; Monika M. Esser (AOSIS, 2016)
Background: Optimal infant- and young child-feeding practices are crucial for nutritional status, growth, development, health and, ultimately, survival. Human breast milk is optimal nutrition for all infants. Complementary food introduced at the correct age is part of optimal feeding practices. In South Africa, widespread access to antiretrovirals and a programme to prevent mother-to-child transmission of HIV have reduced HIV infection in infants and increased the number of HIV-exposed uninfected (HEU) infants. However, little is known about the feeding practices and nutritional status of HEU and HIV-unexposed (HU) infants. Objective: To assess the feeding practices and nutritional status of HIV-exposed and HIV-unexposed (HU) infants in the Western Cape. Design: Prospective substudy on feeding practices nested in a pilot study investigating the innate immune abnormalities in HEU infants compared to HU infants. The main study commenced at week 2 of life with the nutrition component added from 6 months. Information on children's dietary intake was obtained at each visit from the caregiver, mainly the mother. Head circumference, weight and length were recorded at each visit. Data were obtained from 6-, 12- and 18-month visits. World Health Organization feeding practice indicators and nutrition indicators were utilised. Setting: Tygerberg Academic Hospital, Western Cape. Mothers were recruited from the postnatal wards. Subjects: Forty-seven mother-infant pairs, 25 HEU and 22 HU infants, participated in this nutritional substudy. Eight (17%) infants, one HU and seven HEU, were lost to follow-up over the next 12 months. The HEU children were mainly Xhosa (76%) and HU were mainly mixed race (77%). Results: The participants were from poor socio-economic backgrounds. In both groups, adherence to breastfeeding recommendations was low with suboptimal dietary diversity. We noted a high rate of sugar- and salt-containing snacks given from a young age. The HU group had poorer anthropometric and nutritional indicators not explained by nutritional factors alone. However, alcohol and tobacco use was much higher amongst the HU mothers. Conclusion: Adherence to breastfeeding recommendations was low. Ethnicity and cultural milieu may have influenced feeding choices and growth. Further research is needed to understand possible reasons for the poorer nutritional and anthropometric indicators in the HU group. Keywords: Feeding practices; Nutritional status; HIV-exposed